Pollution halo impact in context of productive capacities, energy poverty, urbanization, and institutional quality. - Yuqiang Mo; Ghulam Rasool Madni (PLoS ONE)
The Belt and Road Initiative (BRI) represents a substantial development strategy spearheaded by China. Its central aim is to foster connectivity across a vast geographical area that includes countries spanning Asia, Europe, and Africa. This project played a pivotal role to develop the region on the one side and also raised serious environmental concerns on the other side. There is extensive literature explored the various dimensions affecting the environment in BRI partner countries but there is hardly any study examining the impact of productive capacities, energy poverty, FDI, urbanization, and institutional quality on CO2 emission in the BRI region. Moreover, pollution halo impact is also explored so this study used panel data of 52 nations engaged in the BRI covering time span of 2001-2022 by applying OLS, Difference GMM, System GMM, Cross sectional-ARDL techniques. The results suggest that enhancing productive capacities, FDI and institutional quality significantly reduces carbon emissions in the region, while energy poverty, urbanization and economic growth is linked to higher carbon emissions. Moreover, 'pollution halo effect' is proved because of adoption of eco-friendly technologies through foreign corporations lead to reduction in carbon emission. The study advocates for policy measures that emphasize the promotion of productive capacities, the utilization of renewable energy sources, the adoption of practices regarding sustainable urban development, the implementation of efficient institutional structure, and inflow of eco-friendly technology through FDI.